Consolidación y suspensión: mecanismos procesales ante los arbitrajes de partes y contratos múltiples - de la Flor Puccinelli, Nicolas (2017)
The commercial operations of the modern world are complex and often present a series of equally sophisticated disputes. The old contractual models and their remedies are not sufficient to cover the current dynamics, this is the case of related operations that require efficient tools for their solution.In this context, the author develops a series of techniques or mechanisms for the efficient and effective solution of the identified problems, consolidation and suspension. It proposes that these mechanisms respond to the contractual mechanics of the current trade, which involves a series of intricate and related relationships, grouping in a single process the solution of the controversy.Likewise, the advantages and elements required by these mechanisms to operate will be analyzed.